Allogenic mesenchymal stem cell-conditioned medium does not affect sperm parameters and mitigates early endometrial inflammatory responses in mares - Tongu, Eriky Akio de Oliveira [UNESP]; Segabinazzi, Lorenzo G.T.M. [UNESP]; Alvarenga, Marina Landim [UNESP]; Monteiro, Aldine [UNESP]; Papa, Frederico Ozanam [UNESP]; Alvarenga, Marco Antonio [UNESP] (Elsevier, 2021)
This study aimed to evaluate the effects of mesenchymal stem cell-conditioned medium (MSC-CM) on sperm parameters, intrauterine polymorphonuclear neutrophils (PMN), intrauterine fluid accumulation (IUF), and fertility in mares. In experiment 1, two ejaculates from ten stallions were extended to 50 million sperm/mL using a milk-based extender. Thereafter, 20 mL of extended semen was added of MSC-CM as follows: 0, 5, 10, 15, and 20 mL. Sperm kinetics and plasma membrane integrity were evaluated immediately after dilution (T0) and 2 h post-incubation at 37 °C (T2). In experiment 2, mares characterized as resistant (n = 13) or susceptible (n = 7) to endometritis were inseminated with fresh semen 24 h post-induction of ovulation in two (Control and CM-1) and three (Control, CM-1, and CM-2) cycles in a crossover, as follows: control, no pharmacological interference; CM-1, supplementation of semen insemination dose at 3:4 (v:v, MSC-CM:semen); CM-2, 30 mL of MSC-CM was infused into the uterus 24 h before insemination. Endometrial cytology and uterine fluid were collected 6 and 24 h after insemination to evaluate the number of PMNs and concentrations of interleukins IL6, IL10, and TNFα. IUF was determined by ultrasonography 24 and 48 h after insemination. Pregnancy status was diagnosed 14 days after ovulation. The addition of MSC-CM to semen did not influence sperm parameters at T0 and T2 (P > 0.05) and reduced (CM-1; P < 0.05) the number of PMNs at 6 h post-insemination in resistant mares. In susceptible mares, PMNs at 6 and 24 h post-insemination, as well as IUF were reduced (P < 0.05) in both treated cycles (CM-1 and CM-2). In addition, MSC-CM downregulated IL6 and upregulated IL10 concentrations in the uterus of susceptible mares after insemination. There were no differences in fertility rates among groups both in resistant (Control, 77%, 10/13; CM-1, 62%, 8/13) and susceptible mares (Control, 42.8%, 3/7; CM-1, 57.1%, 4/7; CM-2, 85.7%. 6/7). In conclusion, MSC-CM did not affect sperm parameters when mixed with diluted semen, and reduced post-insemination inflammatory responses in mares.
Keywords: Cell-therapy; Endometritis; Equine; Fertility; Uterus